2021
DOI: 10.1177/15269248211024601
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rivaroxaban and Apixaban on Tacrolimus Trough Levels

Abstract: The solid organ transplant community is slow to adopt the routine practice of using direct oral anticoagulants. Rivaroxaban and apixaban share common metabolic pathways with tacrolimus. This study aimed to clarify the impact of rivaroxaban/apixaban on tacrolimus troughs. Fifty solid organ transplant recipients with concomitant use of tacrolimus and rivaroxaban/apixaban were retrospectively assessed for changes in tacrolimus troughs and dose. Average dose-adjusted tacrolimus troughs and average tacrolimus total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In a similar study, Scheibner et al 99 retrospectively evaluated 50 SOT recipients receiving TAC with either rivaroxaban (n = 18) or apixaban (n = 32) for changes in TAC trough levels and doses. The median dose-adjusted TAC trough and total daily dose were not statistically different pre-DOAC use and post-DOAC use.…”
Section: Posttransplant Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a similar study, Scheibner et al 99 retrospectively evaluated 50 SOT recipients receiving TAC with either rivaroxaban (n = 18) or apixaban (n = 32) for changes in TAC trough levels and doses. The median dose-adjusted TAC trough and total daily dose were not statistically different pre-DOAC use and post-DOAC use.…”
Section: Posttransplant Considerationsmentioning
confidence: 99%
“…The authors concluded that it was unlikely that rivaroxaban or apixaban have an impact on the exposure of TAC in SOT recipients. 99…”
Section: Posttransplant Considerationsmentioning
confidence: 99%
See 2 more Smart Citations